Galactose‐α‐1,3‐galactose‐presenting bacterial families are associated with resistance to experimental avian malaria infection - R. K. Noble; T. R. Kelly; C. R. Lattin (Journal of Avian Biology)
The gut microbiome can contribute to host health through defense against pathogens. However, links between the host gut microbiome and resistance to infection have been primarily investigated in humans and lab‐bred rodents, so we do not know to what extent this relationship exists in wild animals. To fill this knowledge gap, we used an experimental malaria inoculation with Plasmodium relictum in wild‐caught house sparrows Passer domesticus (n = 18) to examine interactions of the host gut microbiome and resistance to avian malaria infection. Before and after inoculation, we collected blood samples to quantify circulating parasitemia and fecal samples to evaluate the gut microbiome through amplification and sequencing of the V4 region of the bacterial 16S rRNA gene. We found that gut microbiome alpha diversity (species richness and evenness) and beta diversity (community composition) were not significantly different between infected and resistant sparrows prior to or during malaria infection. However, we identified several indicator ASVs that occurred at higher prevalence and proportional abundance in malaria‐resistant sparrows, most of which were from the family Lactobacillaceae that is hypothesized to confer resistance to malaria through inducing the production of anti‐α‐Gal antibodies. Future studies should experimentally manipulate the composition of the avian gut microbiome to causally investigate the relationship between specific bacterial taxa in the host gut microbiome and resistance to avian malaria infection.